The poetry of translation from Chaucer & Petrarch to Homer & Logue - Reynolds, Matthew (Oxford University Press, 2011)
This is a wide-ranging book which launches a new theory of poetry translation and pursues it through readings of poem-translations from across the history of English literature. It engages with the key debates in translation studies, and offers new interpretations of major works.